Meaning making and communication in the multimodal age: ideas for language teachers - Álvarez Valencia, José Aldemar (Colombian Applied Linguistics Journal, 2016)
Contemporary societies are grappling with the social changes caused by the current communication landscape and complex textual habitats. To account for this complexity in meaning-making practices, some scholars have proposed the multimodal approach. This paper intends to introduce the core concepts of multimodality including semiotic resources, modes of communication, and intersemiotic relationships. It provides practical applications of multimodal analyses by examining printed and digital pages of educational materials. The final section proposes a set of recommendations to integrate the multimodal perspective in language classes, highlighting the need to make students aware of the new dynamics of meaning making, meaning negotiation, and meaning distribution.